Выражение cos⁡(π- α)+ cos⁡(3/2 π+ α) /1+2 cos⁡(-α)∙sin⁡(- α)

камила20053 камила20053    1   23.08.2019 23:40    0

Ответы
Raffee Raffee  08.09.2020 23:18
Cos(π-α)=-cosα
cos(3π/2+α)=sinα
cos(-α)=cosα
sin(-α)=-sinα
sin²α+cos²α=1
поэтому
\frac{cos(\pi- \alpha )+cos(3 \pi /2+ \alpha )}{1+2cos(- \alpha )sin(- \alpha )} =\frac{-cos \alpha +sin \alpha}{1-2cos \alpha sin \alpha } =\frac{ sin \alpha-cos \alpha}{sin^2 \alpha +cos^2 \alpha -2cos \alpha sin \alpha }= \\ =\frac{ sin \alpha-cos \alpha}{(sin \alpha -cos \alpha)^ 2 }=\frac{ 1}{sin \alpha -cos \alpha }
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра